MENGGAGAS MADING SEBAGAI MEDIA KOMUNIKASI PARTISIPATIF DI SDN TANJUNG ANOM 3 NGANJUK - Indrayani, Inri Inggrit; Priyowidodo, Gatut; S. Luhukay, Marsefio (SHARE: "SHaring - Action - REflection", 2015)
As the simplest communication media, mading is a significant medium to encourage creativity, imagination and provide opportunity for students to be expresive. In fact, there arenât many schools utilizing mading as a communication medium to empower students. Mading management that empowers students will also provide benefits to improve the literacy skills and build a culture of teamwork. This paper aims to examine the utilization of mading as a learning medium for students at SDN Tanjung Anom 3 Nganjuk. Mading is merely informative medium or one-way communication from the teacher to the students. Mading utilization is emphasized as a bulletin board only. Community service activities were implemented then, aimed to put mading as a medium of participatory communication in order to foster synergies between school as educational institution and the needs of the students. The results of the training has been done in SDN Tanjung Anom 3 shows that the management of mading within involvement of students will make them become more creative, expressive and imaginative. Students further become collaborative and explorative in mading management thus the function of mading as a medium of two way communication might be implemented.